PENGARUH PERSEPSI EKSTERNAL PRESTISE TERHADAP PERILAKU MENYIMPANG DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. TELKOMUNIKASI INDONESIA CABANG BANDA ACEH - Safira Ulfa; Sofyan Sofyan (Departemen Manajemen, 2020)
This study aims to determine and explain the effect of Prestige External Perception on Deviant Behavior with Job Satisfaction as a Mediation Variable in PT. Indonesian Telecommunications Communication Branch Banda Aceh. The type of research used in this study is explanatory with a quantitative approach. The population of this study is employees at PT. Telkom Indonesia Banda Aceh Branch. The sample was taken as many as 127 respondents. Hypothesis testing uses Hierarchical Linear Modeling analysis with the help of Spss 20.0 for Windows. The test results show that Prestige External Perception has a negative effect on Deviant Behavior in PT employees. Telkom Indonesia Banda Aceh Branch. Prestige External Perception has a negative effect on Employee Welfare. Job Satisfaction is positively related to Deviant Behavior. Job Satisfaction mediates partially (partial mediation) Prestige External Perception of Deviant Behavior.